2021
DOI: 10.1038/s41598-021-81195-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-induced thermopower inversion in nanocrystalline SnSe thin film

Abstract: Given the growing demand for environmentally friendly energy sources, thermoelectric energy conversion has attracted increased interest as a promising CO2-free technology. SnSe single crystals have attracted attention as a next generation thermoelectric material due to outstanding thermoelectric properties arising from ultralow thermal conductivity. For practical applications, on the other hand, polycrystalline SnSe should be also focused because the production cost and the flexibility for applications are imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Shimizu et al. [ 132 ] found that the thermopower of SnSe was inverted after long atmospheric annealing at ≈480 K due to surface oxidation. In addition, the resistance of the sample reduces with increasing annealing time.…”
Section: Properties and Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Shimizu et al. [ 132 ] found that the thermopower of SnSe was inverted after long atmospheric annealing at ≈480 K due to surface oxidation. In addition, the resistance of the sample reduces with increasing annealing time.…”
Section: Properties and Modulationmentioning
confidence: 99%
“…Zhong et al [131] showed that SnSe NSs could completely transform into SnO 2-x NSs after 1 h annealing at 500 °C. Shimizu et al [132] found that the thermopower of SnSe was inverted after long atmospheric annealing at ≈480 K due to surface oxidation. In addition, the resistance of the sample reduces with increasing annealing time.…”
Section: Oxidation Behaviormentioning
confidence: 99%
“…The Seebeck coefficient changed its polarity with the annealing for different time duration. The freshly deposited SnSe thin films had a S value of +757 µVK −1 , which changed to −427 µVK −1 for the films annealed for 11,500 min in the air [234]. The thermoelectric transport of thin films is influenced by various parameters such as deposition time [235], deposition temperature [236], distance between the target to the substrate as well as annealing time and temperature [237,238].…”
Section: Dimensionality Effectmentioning
confidence: 99%
“…From the Figure 4(a), it is noticeable that the absorption coefficient (α) increases as the T p-f increases, and its value for all the obtained thin films is larger than (10 4 ), which indicates the direct transition of electrons. Tauc's relation [27] was applied to determine the optical band gap energy for the SnSe thin films:…”
Section: Absorption Coefficientmentioning
confidence: 99%